On Board Excavator Dilution Detector - Benjamin Cebrian (International Society of Explosives Engineers)
Traditional dilution control systems range from computer modeling, use of physical markers on the field as polypipes to a technology that marks some control points where displacement is measured. The latter includes walking over a muckpile which is prohibited by some mining companies as a safety measure. The new technology presented in this paper is a patented system that is installed on board excavators (backhoe or front shovel types). Several control points are set along ore/waste contacts and their position is uploaded on the corresponding shovel. The operator proceeds on mucking until he is alerted when reaching any of the several control points previously located in the blast patterns and that have moved with the muckpile. A case study is presented at a high grade copper mine, were unique 3D shapes are showing as a result of using an on-board excavator dilution control system. Both ore-loss or dilution cost of opportunities are analyzed.